Risk Management Readiness of Vietnamese SMEs under the Eu- German Supply Chain Due Diligence Act - Thang , Tran Duc; Nhung, Nguyen Thi Hong (Journal of Ecohumanism, 2024)
The implementation of the German Supply Chain Due Diligence Act and the European Union’s Corporate Sustainability Due Diligence Directive has significant implications for the Vietnamese small and medium-sized enterprises (SMEs) integrated into global supply chains. This study assesses the readiness of the Vietnamese SMEs in adopting risk management practices to comply with these regulations. Utilizing a mixed-methods approach, the study reveals limited awareness and implementation of due diligence requirements among the SMEs, highlighting the need for targeted support and capacity-building initiatives.